MENGOPTIMALKAN MANAJEMEN KEUANGAN PERUSAHAAN KONVEKSI DENGAN TEKNOLOGI AI - Agustin Ekadjaja; Jeslyn Nikita Japry (Jurnal Serina Abdimas, 2026)
In the rapidly evolving digital era, the implementation of artificial intelligence (AI) has become a key factor in enhancing operational efficiency, including financial management in garment manufacturing businesses. Cut, Make, and Trim (CMT) SMEs face challenges in managing cash flow, optimizing expenses, and improving profitability amid intense competition in the manufacturing industry. AI technology offers innovative solutions in financial data processing, market trend prediction, and data-driven decision-making. However, its implementation still encounters obstacles, such as integration with legacy systems, the need for high-quality data, and the readiness of human resources to manage AI-driven systems. This PKM activity aims to explore the benefits of AI adoption in financial management for CMT SMEs and identify optimal strategies to overcome implementation challenges. The methods used include case study analysis of several garment companies that have integrated AI into their financial operations, interviews with key stakeholders, and simulations of AI-based predictive models. The findings indicate that AI enhances financial planning accuracy, reduces financial risks, and helps businesses improve operational efficiency. With the right AI adoption strategies, CMT SMEs can become more adaptive to market dynamics and ensure sustainable business growth. Dalam era digital yang berkembang pesat, penerapan teknologi kecerdasan buatan (AI) menjadi kunci dalam meningkatkan efisiensi operasional, termasuk dalam manajemen keuangan perusahaan konveksi. UMKM Cut, Make, and Trim (CMT) menghadapi tantangan dalam mengelola arus kas, mengoptimalkan pengeluaran, serta meningkatkan profitabilitas di tengah persaingan industri manufaktur. Teknologi AI menawarkan solusi inovatif dalam analisis data keuangan, prediksi tren pasar, serta pengambilan keputusan berbasis analitik. Namun, implementasinya masih menghadapi hambatan, seperti integrasi dengan sistem lama, kebutuhan akan data berkualitas tinggi, serta kesiapan sumber daya manusia dalam mengelola sistem berbasis AI. Kegiatan PKM ini bertujuan untuk mengeksplorasi manfaat penggunaan AI dalam manajemen keuangan UMKM CMT serta mengidentifikasi strategi optimal untuk mengatasi kendala implementasi. Metode yang digunakan mencakup analisis studi kasus dari beberapa perusahaan konveksi yang telah menerapkan AI, wawancara dengan pemangku kepentingan, serta simulasi model prediktif berbasis AI. Hasil penelitian menunjukkan bahwa AI mampu meningkatkan akurasi perencanaan keuangan, mengurangi risiko finansial, serta mengoptimalkan efisiensi operasional. Dengan adopsi teknologi AI yang tepat, UMKM CMT dapat lebih adaptif menghadapi dinamika pasar dan memastikan pertumbuhan bisnis yang berkelanjutan.